2013
DOI: 10.1016/j.bbamcr.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

The FOX transcription factor Hcm1 regulates oxidative metabolism in response to early nutrient limitation in yeast. Role of Snf1 and Tor1/Sch9 kinases

Abstract: Within Saccharomyces cerevisiae, Hcm1is a member of the forkhead transcription factor family with a role in chromosome organization. Our group recently described its involvement in mitochondrial biogenesis and stress resistance, and reports here that Hcm1 played a role in adaptation to respiratory metabolism when glucose or nitrogen was decreased. Regulation of Hcm1 activity occurs in at least three ways: i) protein quantity, ii) subcellular localization, and iii) transcriptional activity. Transcriptional acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…It was recently reported that Snf1 phosphorylates the yeast Forkhead protein, Hcm1, in response to stress, facilitating shuttling of Hcm1 from the cytosol to the nucleus (55). Hcm1 is tightly linked to Fkh1/2 activity as it transcribes FKH1 and FKH2 during late S phase (70).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was recently reported that Snf1 phosphorylates the yeast Forkhead protein, Hcm1, in response to stress, facilitating shuttling of Hcm1 from the cytosol to the nucleus (55). Hcm1 is tightly linked to Fkh1/2 activity as it transcribes FKH1 and FKH2 during late S phase (70).…”
Section: Discussionmentioning
confidence: 99%
“…An evolutionarily conserved stress response network utilizing AMPK and Forkhead proteins has been described (53,55,57). In yeast, it was shown that the Forkhead protein Hcm1, but not Fkh1 or Fkh2, was phosphorylated by Snf1 under stress conditions (55).…”
Section: Enhanced Stress Resistance Conferred By the Uba Mutation Is mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Snf1 and TORC1 may act at similar steps in the regulation of Msn2 (Mayordomo et al 2002). Finally, TORC1 and Snf1 phosphorylate Hcm1 to inhibit and stimulate, respectively, nuclear translocation of this transcription factor (Rodriguez-Colman et al 2013). The nuclear translocation of Hcm1 leads to a shift in metabolism from fermentation to respiration.…”
Section: Opposing Roles Of Torc1 and Ampk In Controlling Agingmentioning
confidence: 99%
“…Protein extracts were prepared for gel electrophoresis. Phos-tag gel electrophoresis was conducted as described previously (31). Briefly, ϳ2 ϫ 10 8 to 4 ϫ 10 8 cells for each sample or time point were used for extraction.…”
mentioning
confidence: 99%